Take a tin : 16 beautiful projects for your home - Schlee, Jemima (Guild of Master Craftsman Publications, 2016)
This collection of original and innovative projects celebrate the humble tin. Jemima Schlee shows you how to cut, paint, pierce and spray with her clear and easy-to-follow step-by-step instructions. All the techniques, templates and equipment required are provided so all you need to worry about is getting that tin collection started.